THE EFFECT OF WORK DISCIPLINE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE DURING WORK FROM HOME POLICIES (CASE STUDY OF PT PLN (PERSERO) PUSHARLIS UP2W III BANDUNG) - Melinda, Bella Putri; Ramadhan, Dandy Rizky; Sumirat, Fariz Muhammad; Sumirat, Firdauz Muhammad; Maulana, Irwan; Handayani, Rini (CENTRAL ASIA AND THE CAUCASUS, 2022)
The COVID-19 pandemic became a new paradigm for companies to carry out work patterns by implementing Work From Home (WFH) activities. Despite the policy changes, the company always requires employees to remain disciplined and on the other hand the company needs to pay attention to job satisfaction in order to improve good performance and achieve company success. The purpose of this study is to find out the influence of work discipline and job satisfaction on employee performance during WFH policy on PT PLN (Persero) Pusharlis UP2W III Bandung. Research methods are used descriptively and verification with data collection techniques through interviews, observations and questionnaires. The population in this study is all employees of PT PLN (Persero) Pusharlis UP2W III Bandung. The sample in this study was a permanent employee of PT PLN (Persero) Pusharlis UP2W III Bandung with a minimum sample of 100 respondents. Data analysis using multiple linear regression with the help of SPSS 25 applications. The results showed that there was a positive and significant influence between the variables of work discipline and job satisfaction on employee performance.